1998
DOI: 10.1002/(sici)1098-1136(199809)24:1<141::aid-glia13>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and functional blocking of gap junction hemichannels (connexons) with antibodies against external loop domains in astrocytes

Abstract: Astrocytes constitute a metabolically and electrically coupled syncytium which is essential for the regulation of ionic homeostasis of the interstitial brain fluid and for coordinating responses to neuronal activities. The structural avenues that couple individual astrocytes are provided by gap junctions which consist of transmembraneous channels that bridge the extracellular space. Each gap junction channel is composed of two hemichannels (connexons) that dock to each other via their extracellular loops. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 44 publications
8
82
0
Order By: Relevance
“…Thus, travelling [Ca 2+ ] i waves can also be caused by release of nucleotides, stimulation of P2 receptors and generation of further nucleotide release to feed wave propagation. Travelling [Ca 2+ ] i waves appear to be dependent on the expression of gap junction proteins, raising the question of whether expression of connexins may modulate nucleotide release [90,91]. Forced expression of different connexins (Cx43, Cx32, Cx26) caused a greatly increased UTP-stimulated ATP release in different cell types [90].…”
Section: A Link To Connexins Pannexins and Atp-permeable Hemichannelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, travelling [Ca 2+ ] i waves can also be caused by release of nucleotides, stimulation of P2 receptors and generation of further nucleotide release to feed wave propagation. Travelling [Ca 2+ ] i waves appear to be dependent on the expression of gap junction proteins, raising the question of whether expression of connexins may modulate nucleotide release [90,91]. Forced expression of different connexins (Cx43, Cx32, Cx26) caused a greatly increased UTP-stimulated ATP release in different cell types [90].…”
Section: A Link To Connexins Pannexins and Atp-permeable Hemichannelsmentioning
confidence: 99%
“…This requires that connexin molecules, in addition to building gap junctions between cells, also localise in the plasma membrane as hemichannels. Using well-characterised antibodies against the extracellular loops of connexins, strong evidence for hemichannel localisation in cellular processes and filipodia of astrocytes has been provided [91]. Lowering extracellular Ca 2+ triggered the uptake of small (>1 kDa) fluid phase fluorophores, and this could be blocked with antibodies against connexins [91].…”
Section: A Link To Connexins Pannexins and Atp-permeable Hemichannelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no direct measure of the number of hemichannels inserted in the membrane using connexins labeled with enhanced green-fluorescent protein (eGFP) [22], reaction with antibodies to the extracellular loop indicates substantial and readily visualized accessibility of extracellular epitopes of Cx43 hemichannels in astrocytes [52]. Thus, the observations that only a few hemichannels open in Cx43-expressing cells indicate that open probability, P o , is very low.…”
Section: Hemichannel Open Probability Is Smallmentioning
confidence: 99%
“…Consistent with this hypothesis, biochemical, immunolabeling, and expression studies revealed that connexons may be inserted in nonjunctional regions of the cell membrane (Musil et al 1991;Paul et al 1991;De Vries et al 1992). Other studies showed that leakage of cytosolic molecules and uptake of extracellular, membrane-impermeant tracers may be abolished by drugs or conditions blocking gap junction channels (Liu et al 1998;Hofer and Dermietzel 1998;Kondo et al 2000;Quist et al 2000). Finally, electrophysiology of single cells identified currents with voltage sensitivity and unitary conductances approximatively as expected for half junctional channels, made of unpaired connexons (Harris 2001;Stout et al 2004;Saez et al 2005;Spray et al 2006).…”
Section: Introductionmentioning
confidence: 99%